Type B aortic dissection presenting as a left-sided hemothorax in a patient with a low-risk probability - Abduluah Alramyan; Fahd Alkhalifah (Wolters Kluwer Medknow Publications, 2021)
The differential diagnosis of isolated pleural effusion is very wide. Unilateral hemothorax carry the same wide differentials. Taking systematic approach can lead to diagnosis in the majority of cases. We presented a case of unilateral hemothroax in a gentleman with minimal symptoms and unhelpful clinical exam. Despite his low risk, he turned to have type B aortic dissection presenting as left sided hemothorax, which is a rare presentation. We presented the clinical course the patient went through and finished with brief discussion on thoracic aortic dissection and its relation to hemothorax.